2018
DOI: 10.1093/jbcr/iry036
|View full text |Cite
|
Sign up to set email alerts
|

Renal Replacement Therapy in Severe Burns: A Multicenter Observational Study

Abstract: Acute kidney injury (AKI) after severe burns is historically associated with a high mortality. Over the past two decades, various modes of renal replacement therapy (RRT) have been used in this population. The purpose of this multicenter study was to evaluate demographic, treatment, and outcomes data among severe burn patients treated with RRT collectively at various burn centers around the United States. After institutional review board approval, a multicenter observational study was conducted. All adult pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 21 publications
4
34
0
Order By: Relevance
“…Among the 58 included studies, 23 were from North America (1, 4, 9, 17-19, 27, 29, 31, 33, 34, 36, 37, 42-44, 48-50, 54, 59, 61, 62), 18 were from Asia (5, 7, 10, 11, 22, 24-26, 28, 39, 40, 46, 47, 51, 52, 58, 64, 66), 15 were from European countries (6, 20, 21, 23, 30, 35, 38, 45, 53, 55-57, 60, 65, 67), one was from South America (32), one was Africa (41). A total of 12 studies could not be used for analysis of the prevalence of RRT, seven of which only reported on RRT patients (11,18,21,37,40,43,45), four of which were RCT studies (9, 10, 51, 52), and the remaining one of which were historical controls (44). Most of the 58 studies (41/60) were retrospective cohort studies, but 12 were prospective cohort studies (7,35,39,41,43,46,47,50,57,58,64,65), and 5 RCT studies (9, 10, 51, 52, 56).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 58 included studies, 23 were from North America (1, 4, 9, 17-19, 27, 29, 31, 33, 34, 36, 37, 42-44, 48-50, 54, 59, 61, 62), 18 were from Asia (5, 7, 10, 11, 22, 24-26, 28, 39, 40, 46, 47, 51, 52, 58, 64, 66), 15 were from European countries (6, 20, 21, 23, 30, 35, 38, 45, 53, 55-57, 60, 65, 67), one was from South America (32), one was Africa (41). A total of 12 studies could not be used for analysis of the prevalence of RRT, seven of which only reported on RRT patients (11,18,21,37,40,43,45), four of which were RCT studies (9, 10, 51, 52), and the remaining one of which were historical controls (44). Most of the 58 studies (41/60) were retrospective cohort studies, but 12 were prospective cohort studies (7,35,39,41,43,46,47,50,57,58,64,65), and 5 RCT studies (9, 10, 51, 52, 56).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study found an odds of dialysis of 2.40 in burn patients who developed AKI compared with the general Finnish population (71). Eleven studies followed up the long-term renal outcomes of burn patients who survived RRT (9,18,19,21,27,30,34,36,37,50,54). A total of 184 patients survived after renal replacement therapy; 64.13% of them (118/184) were dialysis-independent after discharge, 25% (46/184) needed temporary required dialysis, and 10.87% (20/184) needed long-term dialysis (more than 6 months after discharge).…”
Section: Renal Outcomementioning
confidence: 99%
“…HV and VNOS injuries are associated with renal dysfunction in 13.9% and 4.2% of cases respectively [ 1 ]. Acute kidney injury requiring RRT is associated with 50% mortality in patients with severe burns [ 7 ]. Chung et al appreciated 30% absolute reduction in mortality in burn patients placed on early RRT for acute indications compared to historical controls that were not [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury requiring RRT is associated with 50% mortality in patients with severe burns [ 7 ]. Chung et al appreciated 30% absolute reduction in mortality in burn patients placed on early RRT for acute indications compared to historical controls that were not [ 7 , 8 ]. Furthermore, 90% of survivors experienced renal recovery [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation